Assessment Pregnant Women’s Knowledge Regarding Syphilis at Primary Health care centers in Baghdad City - kahtan, alaa; majeed, iqbal (Iraqi National Journal of Nursing Specialties, 2016)
Objectives: To assess pregnant women’s knowledge regarding syphilisand to find out the relationship between women’s knowledge regarding syphilis infection and demographic and reproductive variables. Methodology: A descriptive analytical study of non probable (purposive sample) of 250 pregnant women during their different gestational ages for the period (October 2nd to April 25th 2013) by using questionnaire format consists of demographic variables and items of women’s knowledge regarding syphilis who are visiting primary health care centers in Al-Kharkh and Al-Rrusafa in Baghdad city. The coefficient reliability of the questionnaire was determined through test and retest approach and content validity through a panel of experts. Data are analyzed using descriptive and inferential statistics. Results: It was revealed that pregnant women have no enough knowledge about Syphilis infection causes, signs and symptoms, mode of transmission, effect of infection upon fetal health and methods of prevention. Recommendations: The study is recommended that primary health care centers should increase pregnant women’s knowledge and awareness who attained primary health care centers in Baghdad city through educational programs and health booklets to increase their knowledge about these dangerous infection and its effect upon pregnancy outcome and mother’s health. Key Words: Knowledge, Pregnant Women, Syphilis